¿Qué memoria(s) para Buenos Aires? Un análisis comparativo de los casos del Santuario de Cromañón y del Espacio para la Memoria y para la Promoción y Defensa de los Derechos Humanos - Palacios, Cecilia; Rodríguez, Anabella (El Colegio de México A.C., 2013)
The city of Buenos Aires is covered with several territorial markers (monuments, memorials, popular altars, etc.) recalling conflictive events and political-social processes in recent history that embody the various memories of its citizens. On the basis of emblematic cases in the Space for Memory (ex esma) and the Cro-Magnon Sanctuary, we explored how these places of memory are inserted in the city’s structure, in quite dissimilar locations and functions that nevertheless identify them as icons of memory and commemoration. We explore the different ways in which memory can be territorialized and even institutionalized in a specific space.